Anna's crossing : an Amish beginnings novel - Fisher, Suzanne Woods (Fisher, Suzanne Woods. Amish beginnings novel, 2015)
"A young Amish woman fends off the matchmaking efforts of her fellow passengers on the Charming Nancy--the ship that brought the first wave of Amish to America in 1737"--